LAPAROSCOPIC LEFT HEMINEPHRECTOMY IN COMPLETE DOUBLE COLLECTING SYSTEM WITH MULTIPLE UPPER MOEITY KIDNEY STONE - Parardya, Aga; Pramod, Sawkar Vijay (Indonesian Journal of Urology, 2015)
Objective: Laparoscopic heminephrectomy was firstly reported by Jordan and Winslow in 1993. Laparoscopic heminephrectomy has recently been described as a feasible procedure for the treatment of poorly functioning renal moiety in the duplex kidney. However, this minimally invasive technique is a complex procedure that has remained confined to the hands of experienced teams, with a limited number of reports of relatively few cases. In Indonesia, it has rarely been done. Material & method: A 49-year-old male with chief complaint of pain at the left flank for 2 months. From IVU, we found double collecting system with left upper moiety kidney stone. Then we performed laparoscopic left heminephrectomy. Result: Operative time was 2 hours 30 minutes with bleeding < 100 mL. Post operative VAS was 3 with paracetamol analgetic. Patient was discharged 5 days after operation without any complaint. Conclusion: Laparoscopic heminephrectomy is safe to treat patient with complete double collecting system with multiple upper moeity kidney stone.